Research note: Increased lipid accumulation within broiler preadipocytes during differentiation in vitro at atmospheric oxygen tension - Jéssica Moraes Cruvinel; Elizabeth S. Greene; Rachel W. Read; Kichoon Lee; Sami Dridi; Paula R. Chen (Poultry Science)
In the broiler industry, intensive genetic selection has been placed on muscle growth which has undesirably led to increased fat accretion. Models of chicken preadipocyte differentiation in vitro have conventionally used incubators without the ability to control oxygen (O2) tension; thus, the cells are exposed to atmospheric (∼20-21%) O2, which is supraphysiological compared to the O2 tension within adipose tissue. The objective of this study was to investigate embryonic broiler preadipocyte differentiation at different O2 tensions, including atmospheric (20%), physiological (5%), and hypoxic (1%). Culture at 1% O2 resulted in increased abundance of HIF1α, a canonical protein stabilized during hypoxia, thus confirming effectiveness of the treatment. Increased accumulation of lipid was observed in preadipocytes cultured in adipogenic differentiation medium compared to the control medium. When considering oxygen tension, lipid accumulation was increased in preadipocytes that were cultured in differentiation medium at 20% O2 compared to 5% or 1% O2. Furthermore, abundance of transcripts related to fatty acid transport and adipogenesis, fatty acid binding protein 4 (FABP4) and peroxisome proliferator-activated receptor gamma (PPARγ), were increased in differentiated preadipocytes cultured at 20% O2 compared to 5% or 1% O2. Abundance of transcripts related to lipid synthesis and oxidation, acyl-CoA synthetase long chain family member 1 (ACSL1) and carnitine palmitoyltransferase 1A (CPT1A), were increased in the differentiation cultures compared to the control cultures. Abundance of glutathione peroxidase 4 (GPX4) was increased in all the differentiation cultures compared to the controls, regardless of oxygen tension; however, differences in the abundance of other antioxidant enzymes were not observed. Overall, exposure to atmospheric oxygen tension promotes lipid accumulation within chicken preadipocytes, which may need to be considered when developing in vitro models of this process.